The cancer-induced lactate load and oncologic remodeling hypothesis: lactate as a driver of biosynthesis and epigenetics in cancer - Aydin, Hüseyin (Frontiers in Oncology, 2025)
BackgroundCancer cells undergo profound metabolic reprogramming to sustain proliferation, redox homeostasis, and epigenetic remodeling. While the Warburg effect and glutaminolysis have long been recognized as central paradigms, the anabolic and regulatory role of lactate under normoxic conditions remains poorly defined.HypothesisThe Cancer-Induced Lactate Load and Oncologic Remodeling (CILLO) hypothesis proposes that lactate, either imported through MCT1 or produced endogenously, is oxidized to pyruvate by LDHB and subsequently carboxylated to oxaloacetate (OAA) by pyruvate carboxylase. OAA then acts as a metabolic hub driving malate-dependent NADPH production, aspartate synthesis for nucleotide metabolism, activation of the serine/glycine/folate cycle, lipogenesis, and S-adenosylmethionine–mediated epigenetic modifications. In this framework, lactate is no longer a mere by-product of glycolysis but a central integrator of anabolic flux, redox balance, and chromatin dynamics.ConclusionThe CILLO hypothesis unifies previously fragmented mechanisms into a coherent paradigm, emphasizing lactate-derived carbon skeletons as active drivers of tumor growth and metabolic plasticity. Key rate-limiting steps—MCT1-mediated uptake, LDHB-dependent oxidation, PC-driven anaplerosis, and PEPCK-M–mediated cataplerosis—emerge as therapeutic nodes for intervention. This model not only advances our understanding of cancer metabolism but also suggests novel strategies for biomarker development, metabolic imaging, and targeted therapies. By reframing lactate as a central determinant of oncologic remodeling, the CILLO hypothesis provides a foundation for translational advances in oncology and personalized medicine.